Medicinal Plant Empowerment Education for Sustainable Welfare of the Kemuning Village Community - Muhammad Anshari; Dienny Redha Rahmani (Borneo Community Development, 2021)
The lack of use of herbal medicines as an alternative for disease prevention and treatment, especially COVID-19 is due to a lack of knowledge about the positive impact of herbal medicines compared to chemical drugs. Education about family medicinal plants (TOGA) is not very well understood by them, because there is nothing that facilitates them to be able to more clearly understand what is meant by TOGA. This program is carried out by educating the importance of making toga as a garden plant and how to make herbal medicine using TOGA around the house. The results obtained are that people are more interested in planting TOGA in their yards and making herbs to maintain daily health. Furthermore, some people see the economic potential that can be developed in planting TOGA and making herbal medicine as a community business development. Thus, it also has the potential to support community-based sustainable development.